Efficacy and Safety of Ginkgo Leaf Extract and Dipyridamole Injection for Ischemic Stroke: A Systematic Review and Meta Analysis - Xue, Ping; Ma, Zhuoya; Liu, Shuguang (Frontiers in Pharmacology, 2019)
Objective: Ginkgo leaf extract and dipyridamole injection (GDI), a kind of Chinese medicine preparation, has been considered as a promising supplementary treatment for ischemic stroke. The aim of this study was to systematically evaluate the clinical efficacy and safety of GDI mediated therapy for ischemic stroke. Methods: PubMed, Cochrane Library, Medline, Embase, Web of Science, Wanfang database, Chinese Scientific Journal Database (VIP), China National Knowledge Infrastructure (CNKI) and Chinese Biological Medicine Database (CBM), were searched systematically for clinical trials of conventional treatments combined with GDI for ischemic stroke. The reported outcomes including overall response, hemorrheology and blood lipid indexes, and adverse events were systematically investigated. Results: Data from thirty-nine trials including 3,182 ischemic stroke patients were involved. The results indicated that, compared with conventional treatments alone, the combination of conventional treatments with GDI obviously improved the overall response (odds ratio [OR] = 4.14, 95% confidence interval [CI] = 3.26-5.25, P < 0.00001), neurological status (National Institutes of Health Stroke Scale, OR = -3.13, 95% CI = -3.98--2.28, P < 0.00001) and activity of daily living (Barthel Index score, OR = 14.10, 95% CI = 9.51-18.68, P < 0.00001) of patients. Moreover, the hemorheology and blood lipids indexes of ischemic stroke patients were also significantly ameliorated after the combined therapy (P < 0.01). The frequency of adverse events did not differ significantly between the two groups (P > 0.05). Conclusion: Evidence from the meta-analysis suggested that the combination of conventional treatments and GDI is safe and more effective in treating ischemic stroke than conventional treatments alone. Therefore, GDI mediated therapy could be recommended as an adjuvant treatment for ischemic stroke.